If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -13) = 8 Reorder the terms: 2(-13 + y) = 8 (-13 * 2 + y * 2) = 8 (-26 + 2y) = 8 Solving -26 + 2y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + 2y = 8 + 26 Combine like terms: -26 + 26 = 0 0 + 2y = 8 + 26 2y = 8 + 26 Combine like terms: 8 + 26 = 34 2y = 34 Divide each side by '2'. y = 17 Simplifying y = 17
| 72=6+6(x-42) | | 3x+5y+15z=3 | | 10-4*5-17= | | 9[3-7(3-5)]= | | 3x+5y+15z=14 | | 4x+5y+15z=1971 | | 3x+5y+15z=1971 | | 4.3(z-8)= | | 4.3(x-8)= | | 22-6x=7-9x | | 10+5x=-14+x | | 10x+5y+15z=1971 | | 10x+5y+15z=3 | | 10x+5y+15z=14 | | 8x-2=5x+5 | | ln(x^2+x)=ln(2x-6) | | 3x^2-7x=x-4 | | 13x+6(4-2x)= | | 5x=3y+9 | | 4x-ax^2=0 | | 4x-3=9x-8 | | -3+-5x=8 | | 2x+3(2)=4 | | 11x-11=4x+2 | | 11x-12x= | | 0=-16t^2+32t+0 | | 0=-16t+32t+0 | | x+(x-20)+(x-10)=180 | | 5x-3=3x-2 | | 5mn+4m+5n+2mn= | | q=8-p | | 5(3x-12)(x+5)=0 |